ANALISIS KINERIA PORTOFOLIO ANTARA GROWTH STOCK DAN VALUE STOCK Studi Empiris pada Saham LQ45 di Bursa Efek Indonesia - , Raden Andita Gunadarma ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research to determine the differences returns, risk, and portofolio performance value stock and growth stock in the company on the Indonesian Stock Exchange. The data used in the this research are the secondary data in the form of shares of LQ45 listing on the Indonesia Stock Exchange (IDX). The samples in this study shares are included in the LQ 45 for 5-year observation period in a row between the years 2007 to 2011 as many as 45 companies (45x5 = 225 data). The techniques used in this sampling with a purposive sampling. This analysis method used was a quantitative analysis of the t-test. While performance of the portofolio measurement using the method of Sharpe and Treynor. The results showed that the performance of the portofolio difference there are value stock and growth stock in the company LQ45 in Indonesia Stock Exchange. Overall returns from 2007 to 2011, growth stock 0,0915, value stock -0,0122 (method Sharpe), growth stock 0,0316, value stock 0,0135 (method Treynor). There are differences in the risk of the portofolio value stock and growth stock in the company LQ45 in Indonesia Stock Exchange. Overall risk from 2007 to 2011 by using standard deviation as a method of calculating the level of risk, the value of growth stock 0,0731 and values stock 0,0841. Growth stock portofolio has superior performance compared to the company's stock value on the Stock Exchange LQ45 Indonesia. Indicated by the value growth stock performance is greater than the value of the stock value 0.0915> -0.0122 (with a sharpe method), and 0.0316> 0.0135 (with Treynor method).